Predictors of smartphone addiction and its effect on quality of life: a cross-sectional study among the young adults in Bangladesh - Zubair Ahmed Ratan; Anne-Maree Parrish; Mohammad Saud Alotaibi; Hassan Hosseinzadeh (Frontiers in Digital Health)
The enigma of smartphone addiction (SA) has plagued academics for the last decade, now scholars believed this behaviour might affect physical and mental wellbeing. SA has become a complex problem, yet to date, there is limited research investigating the predictors of SA and its effect on “health-related quality of life (HRQoL)”. This study aimed to address this gap. The data was gathered from a convenience sample of 440 young adults completed between July 2021 and February 2022 through online survey in Bangladesh. On Logistic regression, after controlling for socio-demographic variables; friend support, process, social and compulsive usage were determined as significant predictors of SA. Those who were smartphone addicted were more presumably to have a lower quality of life. This study has significant implications for designing prevention pro-grams and policy development in relation to predictors of SA and its effect on HRQoL.